2014
DOI: 10.1016/j.brainres.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

FGF-2 induces neuronal death through upregulation of system xc-

Abstract: The cystine/glutamate antiporter (system xc-) transports cystine into cell in exchange for glutamate. Fibroblast growth factor-2 (FGF-2) upregulates system xc- selectively on astrocytes, which leads to increased cystine uptake, the substrate for glutathione production, and increased glutamate release. While increased intracellular glutathione can limit oxidative stress, the increased glutamate release can potentially lead to excitotoxicity to neurons. To test this hypothesis, mixed neuronal and glial cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
1
13
0
1
Order By: Relevance
“…EAAT3 is another subtype of the XAG system, which has little effect on the uptake of Glu in synaptic cleft, but has a high affinity for extracellular Cys. Studies have shown that there was an obvious decrease of GSH level of neurons in EAAT3‐deficient mice, with a higher sensitivity to oxidants . Results of the present study showed that MeHg upregulated EAAT3 transcription level but downregulated the protein expression.…”
Section: Discussionsupporting
confidence: 57%
“…EAAT3 is another subtype of the XAG system, which has little effect on the uptake of Glu in synaptic cleft, but has a high affinity for extracellular Cys. Studies have shown that there was an obvious decrease of GSH level of neurons in EAAT3‐deficient mice, with a higher sensitivity to oxidants . Results of the present study showed that MeHg upregulated EAAT3 transcription level but downregulated the protein expression.…”
Section: Discussionsupporting
confidence: 57%
“…In astrocytes, fibroblast growth factor 2 up‐regulates system x c − by a transcriptional mechanism, whereas IGF‐1 is ineffective (Liu et al . , ). Thus, some of the responses to growth factors might be cell type‐specific.…”
Section: New Insights Into the Regulation Of Xct Expression And Systementioning
confidence: 99%
“…Notably, FGF-2 activates the stress related transcription factor ATF4 in vascular smooth muscle cells [64] and osteoblasts [65]. FGF-2 upregulated GSH synthesis in glial [66] and Sertoli cells [67] and cystine/glutamate transport (system xc-) in astrocytes [68]. These results suggest that cystine transport activity may be upregulated in the presence of FGF-2 in stem cells or differentiating cells via FGF-2/ATF4 signaling, leading to improved survival and growth, however, to our knowledge this hypothesis remains to be investigated.…”
Section: Importance Of Redox Balance In Stem Cell Culturementioning
confidence: 99%